2009
DOI: 10.1016/j.neulet.2008.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Stressful experience has opposite effects on dendritic spines in the hippocampus of cycling versus masculinized females

Abstract: Stress increases associative learning and the density of dendritic spines in the hippocampus of male rats. In contrast, exposure to the same stressor impairs associative learning and reduces spine density in females. These effects in females are most evident when they are in the proestrus phase of the estrous cycle. An injection of testosterone at the time of birth masculinizes the female brain. In adulthood, masculinized females respond like males do to stress, i.e. they learn better. Here, we hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 39 publications
1
33
0
6
Order By: Relevance
“…These diverse morphological effects of stress are not surprising, given the wide array of stress types and contexts (24) coupled with the biological variability of the hippocampus that is being stressed, including gender (53,69,70) and age (41,71). Therefore it is reasonable to propose that the plethora of structural and functional changes provoked by stress might be a result of a broad repertoire of stress-activated mediators acting via numerous mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These diverse morphological effects of stress are not surprising, given the wide array of stress types and contexts (24) coupled with the biological variability of the hippocampus that is being stressed, including gender (53,69,70) and age (41,71). Therefore it is reasonable to propose that the plethora of structural and functional changes provoked by stress might be a result of a broad repertoire of stress-activated mediators acting via numerous mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, to do this, we first investigated hippocampal functional changes following in vivo treatment with chronic nicotine and withdrawal, which may impact the efficacy of these drugs. To do this, evoked responses were recorded from ventral Electrical stimulation of the Schaffer collateral pathway (Figure 5a and b) results in robust activation of the CA1, a region of the hippocampus sensitive to stress-induced synaptic remodeling (Dalla et al, 2009;Joels et al, 2004Joels et al, , 2008McEwen, 2001;McEwen and Magarinos, 2001;Shors et al, 1997Shors et al, , 2001) and shown to be selectively affected in individuals with anxiety disorders (Cole et al, 2010). As shown in Figure 5ci and ii ( þ 10ms), responses evoked in the CA1 by Schaffer collateral stimulation were significantly increased following chronic administration of nicotine relative to saline controls.…”
Section: Alterations In Anxiety-like Behavioral Responses In the Nih mentioning
confidence: 99%
“…Stress also influences CA1 dendritic/spine morphology, with chronic stress increasing CA1 branching [152] and postsynaptic density [215]. Moreover, sex differences in CA1 spine density emerge following an acute stressor, with males expressing increased apical and/or basal spine density compared to females (for review, see [216]), and this effect can be reproduced through the masculinization of females [217]. In addition, CA1 basal spine shape can be influenced by acute stress [218] and chronic stress [173,174] by facilitating the maturation of spines.…”
Section: Sex-specific Effects Of Chronic Stress On Hippocampal Morphomentioning
confidence: 99%